Who Owns the Stock? : Collective and Multiple Property Rights in Animals. - Khazanov, Anatoly M. (Integration and conflict studies., 2012)
The issue of collective and multiple property rights in animals, such as cattle, camels or reindeers, among pastoralists has never been a subject of special cross-cultural and comparative study. Focusing on pastoralist societies in East and West Africa, the Far North and Siberia, and the Eurasian steppes, this volume addresses the issue of property rights and the changes these societies have undergone due to the direct or indirect influence of modernization and globalization processes. The contributors also investigate the interplay of older sets of rights and modern marketing policies; politi.